Organizational Level Responses to the COVID-19 Outbreak: Challenges, Strategies and Framework for Academic Institutions - Biswakarma, Jagannath; Rushworth, Danielle; Srivastava, Gitika; Singh, Gagandeep; Kang, Kyounglim; Das, Subhasish; Anantharaman, Surendra Babu; Aeppli, Meret; Popp, Andrea L.; Bhuyan, Deep Jyoti (Frontiers in Communication, 2021)
The outbreak of the novel coronavirus, severe acute respiratory syndrome (SARS)–CoV-2, has gained unprecedented global attention. SARS-CoV-2, which causes the newly described coronavirus disease 2019 (COVID-19), has affected millions of people and led to over 1.9 million deaths worldwide by the beginning of January 2021. Several governments have opted for lockdown as one of the measures to combat the rapidly increasing number of COVID-19 cases. Academic institutions (i.e., universities, colleges, research centers and national laboratories), which are home to thousands of students, researchers, technicians, and administrative staff, have strictly followed government regulations. Due to the lockdown, the majority of academics are facing various challenges, especially in transitioning from classroom to remote teaching and conducting research activities from a home office. This article from an early-career researchers’ perspective addresses the common challenges that academic institutions have faced and possible strategies they have adopted at the individual organizational level. Furthermore, we propose a framework to facilitate the handling of such crisis in any near future at the organizational level. We hope academics, policymakers and (non) government organizations across the globe will find this perspective a call to better improve the overall infrastructure of academic institutions.